Reconsidering Reconciliation Within Families of Youth Who Sexually Offend - Gervais, Christine L. M. (Journal of interpersonal violence, 2022)
Research on youth sexual offending has focused primarily on its prevalence, risk factors, treatment interventions, and recidivism rates. Thus, there is a need to develop better understandings of the processes towards reconciliation (or the lack thereof) that occur in the context of the collateral consequences of such harm-generating behavior. This qualitative study presents parents? perspectives on the benefits and challenges associated with the implications and outcomes of reconciliation, and of its deprivation among sexually offending youth, victims and their relatives. We analysed in-depth, semi-structured interview data among 16 parents from 10 families in Canada using thematic coding procedures. The findings reveal that in the absence of reconciliation, both relationship repair and rehabilitation are hindered by miscommunication, bitterness, and confusion. By contrast, when meaningful reconciliation occurs, offending youth are better able to take responsibility for their actions, which in many cases led to victim validation and relationship restoration among all affected parties, including immediate and extended relatives. Our research points to the importance of restorative practices in both formal and informal attempts towards accountability, reconciliation, rehabilitation, victim redress, as well as family and community reintegration.